Resilient Aquatic Food System’ rolled out to enhance food security - Cofie, Olufunke O. (Ghanaian Times, 2023)
Ghanaian Times press article: The Minister of Fisheries and Aquaculture Development (MOFAD), Mrs Mavis HawaKoomson, yesterday launched the “Resilient Aquatic Food Systems” initiative in Accra. Aimed at contributing to the country’s food security as well as its developmental agenda, the initiative proposes the integration of aquatic production into water resources management plans to support the country’s food production systems.